Cerebral organoid research for pediatric patients with neurological disorders - Jin Eun; Jung Eun Lee; Seung Ho Yang (Clinical and Experimental Pediatrics)
Cerebral organoids derived from human induced pluripotent stem cells offer a groundbreaking foundation for the analysis of pediatric neurological diseases. Unlike organoids from other somatic systems, cerebral organoids present unique challenges, such as the high sensitivity of neuronal cells to environmental conditions and the complexity of replicating brain-specific architectures. Cerebral organoids replicate the human brain development and pathology, enabling research on conditions such as microcephaly, Rett syndrome, autism spectrum disorders, and brain tumors. This review explores the utility of cerebral organoids for modeling diseases and testing therapeutic interventions. Despite current limitations such as variability and lack of vascularization, recent technological advancements have improved the reliability and application of such interventions. Cerebral organoids provide valuable insight into the mechanisms underlying complex neural disorders and hold promise as novel treatment strategies for pediatric neurological diseases.